The case of the graveyard ghost, and other super-scientific cases - Torrey, Michele; Johansen Newman, Barbara (New York : Dutton Children's Books, 2002)
Now in fifth grade, Drake Doyle and Nell Fossey continue to combine their detective and scientific investigation skills to solve a variety of cases, involving a noisy laundry chute, a ruined flower show, and a ghost.
5.3
3-6
3-6
School Library Journal
Booklist
Horn Book
Keywords: Science -- Methodology -- Fiction; Mystery and detective stories; Science -- Methodology -- Fiction; Mystery fiction